Uji Efek Antihiperglikemik Ekstrak Etil Asetat Daun Binahong (Anredera cordifolia (Ten.) Steenis) pada Mencit Jantan - Andriyani; Yohan Aditya Manik; Febbyasi Megawaty Rangka (Pro-Life, 2023)
Binahong plants has been widely used for treatment many diseases such as diabetic mellitus. Binahong leaves have been studied for secondary metabolic compounds including saponins, flavonoids, steroids, and terpenoids. Objective of the study was to performed in vivo antihyperglycemic test of binahong leaves ethyl acetate extract on blood sugar levels in male mice (Mus musculus). Binahong leaves were macerated with ethyl acetate solvent  and antihyperglycemic test using glucose 40 mg/20 gBW tolerance method. In the study, number of mice  used were 25 mice and divided into 5 treatment groups namely negative control, positive control, ethyl acetate extract of binahong leaves dose of 100 mg/KgBW, 200 mg /KgBW, and 400 mg/KgBW. The results of the study  were ethyl acetate extract of binahong leaves contained secondary metabolites of alkaloids, flavonoids, saponins, and phenols. Data analysis was performed using Statistical Product and Service (SPSS) with the One-Way ANOVA test and post hoc Tukey. The results showed that there was a significant difference (p <0.05) which stated that binahong leaves ethyl acetate extract had good effect  in lowering blood glucose levels with an effective dose 100 mg/KgBW.